Grocery Product Recognition to Aid Visually Impaired People - Machado, André de Lima; Aires, Kelson; Veras, Rodrigo; Britto Neto, Laurindo (Anais do Workshop de Visão Computacional (WVC), 2021)
This paper proposes a new approach in object recognition to assist visually impaired people. This approach achieved accuracy rates higher than the approaches proposed by the authors of the selected datasets. We applied Data Augmentation with other techniques and adjustments to different Pre-trained CNNs (Convolutional Neural Networks). The ResNet-50 based approach achieved the best results in the most recent datasets. This work focused on products that are usually found on grocery store shelves, supermarkets, refrigerators or pantries.